Influence of UV stabilizers on the weathering of PETG and PCTT films. Issue 47 (17th July 2019) - Arangdad, Kiarash; Yildirim, Erol; Detwiler, Andrew; Cleven, Curtis D.; Burk, Christopher; Shamey, Renzo; Pasquinelli, Melissa A.; Freeman, Harold S.; El‐Shafei, Ahmed
ABSTRACT: The influence of two UV photostabilizers on the photostability of Polyethylene‐co‐CHDM‐terephthalate (PETG) and Polycyclohexylenedimethylene‐Co‐TMCD‐terephthalate (PCTT) copolyester films was investigated. Untreated films and films containing stabilizer were irradiated. The resulting films were analyzed by attenuated total reflectance Fourier transform infrared (ATR FTIR) spectroscopy, gel permeation chromatography (GPC), and X‐ray photoelectron spectroscopy (XPS). FTIR spectra of the irradiated films containing Cyasorb 1164 showed less change in intensity of the broad peak corresponding to OH groups, than the films containing Cyasorb 3638, indicating that Cyasorb 1164 is a better photostabilizer for these films. XPS results showed that the decrease in C/O ratio, due to photodegradation, was greater in films containing Cyasorb 3638 compared to those containing Cyasorb 1164. The formation of degradation products was evident from emission spectra arising from extracts of irradiated films based on PCTT +10% Cyasorb 3638, but no degradation products were apparent in extracts from irradiated PCTT +10% Cyasorb 1164. UV‐absorption spectra of Cyasorb 1164 overlap more substantially with the absorption spectra of PETG and PCTT. The results from FTIR, XPS, and GPC analyses of the irradiated PETG and PCTT films demonstrated that Cyasorb 1164 was more effective than Cyasorb 3638 in enhancing resistance to UV‐induced weathering. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48198. Abstract :